2004
DOI: 10.1088/0953-4075/37/6/l02
|View full text |Cite
|
Sign up to set email alerts
|

Angle-dependent decrease of transition probability in sequential photo double-ionization

Abstract: The three-body Coulomb interaction in sequential photo double-ionization, frequently called post-collision interaction (PCI), can lead to a collapse of transition probability if the relative angle between the emitted electrons approaches zero. We have studied this effect for a specially selected atomic system, 4d5/2 photoionization in xenon with subsequent N5–O2,3O2,31S0 Auger decay, and compared the experimental data with results from a quantum mechanical PCI calculation and a classical PCI model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Indeed detailed studies have appeared recently since the introduction of electron / electron coincidence techniques in the field 1 . A partial and non exhaustive list of recent electron / electron coincidence experiments includes valence double ionization of atoms 2 and especially of He 3,4 , of molecules 2,5,6 and especially of H 2 , 7,8 and coincidence studies of Auger 9,10,11,12,13,14,15 and double Auger decays 16,17 . However in most of these examples only a small part of all the processes releasing several electrons is explored as most of the studies have restricted their coincidence detection system or the event analysis to processes where exactly 2 electrons are emitted.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed detailed studies have appeared recently since the introduction of electron / electron coincidence techniques in the field 1 . A partial and non exhaustive list of recent electron / electron coincidence experiments includes valence double ionization of atoms 2 and especially of He 3,4 , of molecules 2,5,6 and especially of H 2 , 7,8 and coincidence studies of Auger 9,10,11,12,13,14,15 and double Auger decays 16,17 . However in most of these examples only a small part of all the processes releasing several electrons is explored as most of the studies have restricted their coincidence detection system or the event analysis to processes where exactly 2 electrons are emitted.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental work on the double photoionization of xenon by Scherer [13] and collaborators demonstrated clearly how PCI plays a role in the interaction of the two continuum (photo and Auger) electrons. Their results were consistent with quantum calculations, which included PCI.…”
mentioning
confidence: 99%
“…The striking theoretical prediction within this model (Vegh 1994a, Vegh 1994b) of strong interference effects in the TDCS for the case when both free electrons have the same kinetic energies has caught researchers attention and was investigated experimentally in the valence outer-shell PDI of Neon (Schaphorst et al 1996) and inner-shell PDI of Xenon , Viefhaus et al 1998, Selles et al 1998. Earlier experimental work (Selles et al 1998) has also shown how the spin state determines the constructive or destructive nature of the interference, which is a consequence of a general selection rule (Maulbetsch and Briggs 1995) already verified in direct PDI of Helium (Schwarzkopf et al 1993). With three charged particles in the final state, PDI requires in addition a detailed delineation of Coulomb interactions in the resulting few body system, also called Post Collision Interactions (PCI).…”
Section: Introductionmentioning
confidence: 98%
“…Photo double-ionization (PDI), the emission of two electrons resulting from single photon absorption, has been intensively studied by many research groups over the past two decades (Mazeau et al 1991, Selles et al 1998, Briggs and Schmidt 2000, Schwarzkopf et al 1993, Dörner et al 1998, Viefhaus et al 1998, Viefhaus et al 1996, Avaldi and Huetz 2005 since it is related to two important topics of modern atomic physics, namely electron correlations and the three-body Coulomb problem. Understanding the role of both effects in the PDI process can be achieved through a detailed description of the Triply Differential Cross Section (TDCS),…”
Section: Introductionmentioning
confidence: 99%